Trade and competition : industrial economist's perspective. - MARTIN, Stephen (1999)
Concludes that theory and empirical evidence both suggest that free trade increases competition, improves market performance in imperfectly competitive international markets, and increases not only overall welfare but also the welfare of individual trading nations. States that there is little reason to think that strategic trade policy - subsidies or export cartels - will improve market performance.